Architectural Green Building Materials for COVID-19 Prevention - Abeer Qasim Jbur (Engineering Research: Perspectives on Recent Advances Vol. 3, 2025)
The architecture of green building design is becoming increasingly important. Green buildings are considered environment-friendly buildings, which are constructed in the healthiest way. Recently, due to the coronavirus pandemic, sustainable design strategies have been targeted to find architectural solutions for developing new materials to reduce the risk of cross-contamination (COVID-19). The emergence of the novel coronavirus is associated with undesired adhesion on the surfaces. Sustainable architecture for hospital design must integrate design strategies to confront the impact of infectious diseases. The aim of this paper is to optimize a novel material that is able to reduce the transmission probability of COVID-19. The composite of high-density polyethene (HDPE) is specifically developed for application in the building, thus requiring an adequate combination of material properties concerning the spread of COVID-19, with mechanical and functional performance of the final products. HDPE is very resilient and tough, has good chemical resistance and high impact strength. The composite preparation conditions allow the formation of a metal powder distribution in the polymer matrix volume to create an architectural functional material. The process of producing the composite material is by compounding (HDPE) with a copper powder. Several tests were performed such as hardenability, density and tensile. The microscopic test observes a significant distribution for the copper powder to provide the polymer surface with the capability to reduce the transmission probability of the viruses. The test results identified the architectural preconditions and considerations of green buildings based on antiviral material selection conditions.